Typology of Sharia-Compliant Business Capital Services to Support the Economic Development of Rural Communities - Rafiqi, Iqbal; Turmidi, Turmidi; Rahman, Holilur; Mujibno, Mujibno; Buchari, Imam; Faizah, Maftuhatul (Assyarikah: Journal of Islamic Economic Business, 2024)
Many business people in underdeveloped villages have difficulty getting business capital. The biggest problem that arises is that there are business people who do not have collateral so it is difficult to get business capital. The existence of PNM Mekaar Syariah in the village community with a business capital distribution service without collateral is very helpful. This research is important to carry out with the aim of analyzing the business capital service system provided by PNM Mekaar Syariah to customers in Ganding District, Sumenep. This research uses a qualitative research approach. The results of this research outline the data that in providing business capital funding assistance, the Ganding branch of PNM Mekaar Syariah does not use collateral but uses a joint responsibility system and provides village communities with business training and supervision of business growth. The impact is that village communities feel served by the government in matters of business capital and hope that services will be optimized and the results will be cheaper.